2015
DOI: 10.3389/fonc.2015.00157
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between Adiponectin and IGF-IR in Breast Cancer

Abstract: Obesity is a chronic and multifactorial disorder that is reaching epidemic proportions. It is characterized by an enlarged mass of adipose tissue caused by a combination of size increase of preexisting adipocytes (hypertrophy) and de novo adipocyte differentiation (hyperplasia). Obesity is related to many metabolic disorders like hypertension, type 2 diabetes, metabolic syndrome, and cardiovascular disease, and it is associated with an increased risk of cancer development in different tissues including breast.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 100 publications
2
60
1
Order By: Relevance
“…For the combined cases, the average beta was 0.25 (SD = 0.10, 95 % CI = 0.21–0.30) in low BMI cases and 0.35 (SD = 0.12, 95 % CI = 0.30–0.41) in high BMI cases and for the HGD/EAC cases, average beta was 0.20 (SD = 0.08, 95 % CI = 0.12–0.27) in low BMI cases and 0.38 (SD = 0.11, 95 % CI = 0.30–0.47) in high BMI cases. Of interest, adiponectin and leptin have also been implicated in obesity-associated cancer [34, 35]; however, we did not observe any differences in the DNA methylation status of genes involved in leptin or adiponectin pathways in any of the esophageal tissue sets in the high vs. low BMI subjects.…”
Section: Resultscontrasting
confidence: 80%
“…For the combined cases, the average beta was 0.25 (SD = 0.10, 95 % CI = 0.21–0.30) in low BMI cases and 0.35 (SD = 0.12, 95 % CI = 0.30–0.41) in high BMI cases and for the HGD/EAC cases, average beta was 0.20 (SD = 0.08, 95 % CI = 0.12–0.27) in low BMI cases and 0.38 (SD = 0.11, 95 % CI = 0.30–0.47) in high BMI cases. Of interest, adiponectin and leptin have also been implicated in obesity-associated cancer [34, 35]; however, we did not observe any differences in the DNA methylation status of genes involved in leptin or adiponectin pathways in any of the esophageal tissue sets in the high vs. low BMI subjects.…”
Section: Resultscontrasting
confidence: 80%
“…Recently, cross-talk between IGF-1 and adiponectin has been found to be associated with breast cancer 38. Mauro et al demonstrated that low levels of adiponectin induce cellular growth independently of IGF-1 in estrogen receptor alpha-positive breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of adiponectin are reduced in obesity in the abdomen, in the male, in postmenopausal women, in high blood pressure, hypertriglyceridemia in type 2 diabetes mellitus and coronary artery disease 71-77. Adiponectin expression is decreased by TNF-a and IL-6, increased by PPARy agonists 78 (Figure 6). Adiponectin exerts a reduction in the proliferation of adipocyte cells, endothelial cells and tumor cells 79,80.…”
Section: Introductionmentioning
confidence: 98%